2011
DOI: 10.1093/cid/cir073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline for the Use of Antimicrobial Agents in Neutropenic Patients with Cancer: 2010 Update by the Infectious Diseases Society of America

Abstract: This document updates and expands the initial Infectious Diseases Society of America (IDSA) Fever and Neutropenia Guideline that was published in 1997 and first updated in 2002. It is intended as a guide for the use of antimicrobial agents in managing patients with cancer who experience chemotherapy-induced fever and neutropenia. Recent advances in antimicrobial drug development and technology, clinical trial results, and extensive clinical experience have informed the approaches and recommendations herein. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
2,742
4
310

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 2,726 publications
(3,204 citation statements)
references
References 313 publications
37
2,742
4
310
Order By: Relevance
“…In the case of neutropenia in the absence of septic shock, studies using modern broad-spectrum antibiotics consistently suggest that, while multidrug therapy to broaden pathogen coverage (e.g., to include Candida species) may be useful, combination therapy using a β-lactam and an aminoglycoside for purposes of accelerating pathogen clearance is not beneficial for less severely ill "low-risk" patients [187]. Combination therapy of this sort for even "high-risk" neutropenic patients (inclusive of hemodynamic instability and organ failure) with sepsis is inconsistently supported by several international expert groups [106,188]. This position against combination therapy for a single pathogen in any form of neutropenic infection emphatically does not preclude the use of multidrug therapy for the purpose of broadening the spectrum of antimicrobial treatment.…”
Section: Combinaɵon Therapymentioning
confidence: 99%
“…In the case of neutropenia in the absence of septic shock, studies using modern broad-spectrum antibiotics consistently suggest that, while multidrug therapy to broaden pathogen coverage (e.g., to include Candida species) may be useful, combination therapy using a β-lactam and an aminoglycoside for purposes of accelerating pathogen clearance is not beneficial for less severely ill "low-risk" patients [187]. Combination therapy of this sort for even "high-risk" neutropenic patients (inclusive of hemodynamic instability and organ failure) with sepsis is inconsistently supported by several international expert groups [106,188]. This position against combination therapy for a single pathogen in any form of neutropenic infection emphatically does not preclude the use of multidrug therapy for the purpose of broadening the spectrum of antimicrobial treatment.…”
Section: Combinaɵon Therapymentioning
confidence: 99%
“…Antifungal prophylaxis has been adopted as a viable approach to prevent IFI and is currently recommended in high-risk patients [4][5][6]. In the current study, voriconazole for primary IFI prophylaxis demonstrated efficacy with a low rate of proven (2.4%) or probable (4.2%) episodes of IFI.…”
Section: Discussionmentioning
confidence: 69%
“…An episode of voriconazole prophylaxis was defined as voriconazole administration to a patient experiencing chemotherapy-induced neutropenia. Patients were considered to have neutropenia when laboratory values indicated an ANC less than 500 cells/ml [4,21]. Neutrophil recovery was defined as an ANC greater than 500 cells/ml for two consecutive days and progressing in an upward direction toward 1000 cells/ml of blood [4,21].…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations